FORMATION OF RESPONSIBLE ATTITUDE OF STUDENTS TO LEARNING CONDITIONS OF THEIR FUTURE COMPETENCE (Pedagogy of Higher and Secondary Education, 2008)
1п article the questions touching problems of formation of the crucial relation of students to the doctrine in higher educational institutions are considered.